Design and Simulation of Earth Based Materials for Indoor Thermal Comfort in Mixed Mode Building Structure - Mohit; Rajbala (International Journal of Scientific Research in Civil Engineering, 2025)
In hot and dry regions like Burkina Faso, achieving indoor thermal comfort with minimal energy use is a key challenge. This study explored the potential of Compressed Earth Blocks (CEB) as a sustainable alternative to cement-based materials for enhancing thermal performance in buildings. Two identical pilot structures were constructed—one with stabilized CEB and the other with cement blocks. Real-time hygrothermal monitoring was carried out from September to November, and building models were developed using Google SketchUp Pro and simulated in EnergyPlus via OpenStudio. Validation of the simulation used ASHRAE indicators (NMBE, CVRMSE, R²), all meeting accepted thresholds. Initial results showed high thermal discomfort in both buildings, with over 79% of annual hours outside comfort levels. However, optimized passive strategies, including improved ventilation and solar absorptivity adjustments, reduced discomfort to 33.3% in the CEB structure. The CEB building demonstrated superior thermal stability, highlighting its suitability for sustainable, climate-resilient construction.